2014
DOI: 10.1136/bmj.g366
|View full text |Cite
|
Sign up to set email alerts
|

Twenty five year follow-up for breast cancer incidence and mortality of the Canadian National Breast Screening Study: randomised screening trial

Abstract: Objective To compare breast cancer incidence and mortality up to 25 years in women aged 40-59 who did or did not undergo mammography screening.Design Follow-up of randomised screening trial by centre coordinators, the study's central office, and linkage to cancer registries and vital statistics databases.Setting 15 screening centres in six Canadian provinces,1980-85 (Nova Scotia, Quebec, Ontario, Manitoba, Alberta, and British Columbia).Participants 89 835 women, aged 40-59, randomly assigned to mammography (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
450
3
19

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 637 publications
(488 citation statements)
references
References 17 publications
16
450
3
19
Order By: Relevance
“…In addition, a recent 25-year follow-up study for BC even questioned the benefit of mammography to women in general. 50 The blood-based HYAL2 methylation can objectively detect BC at very early stage (stages 0 and I, AUC 5 0.89, sensitivity: 64.4%, specificity: 90%, Fig. 5d), and is efficient for women under 50 years as well (age < 50 years, AUC 5 0.87, sensitivity: 62.1%, specificity: 90%, Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a recent 25-year follow-up study for BC even questioned the benefit of mammography to women in general. 50 The blood-based HYAL2 methylation can objectively detect BC at very early stage (stages 0 and I, AUC 5 0.89, sensitivity: 64.4%, specificity: 90%, Fig. 5d), and is efficient for women under 50 years as well (age < 50 years, AUC 5 0.87, sensitivity: 62.1%, specificity: 90%, Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Mammography is also associated with false-positive test results that cause real harm via anxiety and overdiagnosis. 5 Those who argue that a recent negative mammography trial 6 should put an end to the use of mammogram-based breast cancer screening contend that the randomized controlled trial is our best source of data. These Bminimalists^cite the evidence of harm (overdiagnosis and overtreatment).…”
mentioning
confidence: 99%
“…The effects of CBE with and without mammography on downstaging have been the subject of a few RCT where downstaging of disease has been observed, but insufficient follow‐up had elapsed to observe differences in mortality between arms 28, 29. Furthermore, the 25‐year follow‐up of the Canadian National Breast Screening Study found that annual mammography in women aged 40–59 had no additional benefit beyond that of CBE in terms of mortality 30. The inclusion of CBE in the Colombian guidelines was intended to increase detection rates and reduce the chance of interval cancers.…”
Section: Discussionmentioning
confidence: 99%